Sistem Monitoring Jumlah Orang dan Deteksi Logam Pada Tempat Wisata Mengunakan Berbasis Internet of Things - Woro Agus Nurtiyanto; Perani Rosyani; Helena Tamba (KLIK: Kajian Ilmiah Informatika dan Komputer, 2022)
The number of people in a room is an important thing to pay attention to, especially in the current pandemic era. The number of people must not exceed the maximum capacity of the room. Therefore, this study aims to create a system for counting the number of people in a room equipped with a warning alarm if the number of people exceeds the maximum capacity that can be determined through the Blynk application by the room manager. In addition, the room manager can unite the number of people and there is also a metal detection sensor so that people who enter the room do not bring metal items. Ultrasonic sensors are used to detect people entering and leaving the room. Nodemcu ESP8266 as a microcontroller and Blynk application can work to unite a number of people. This tool is an application of IoT (Internet of Things) using a Wi-Fi signal and is made to make it easier for managers of a shop or tourist spot to count and monitor the number of visitors who come. The monitoring system can be made using the NodeMCU ESP8266 microcontroller which has a WiFi module. This system uses an ultrasonic sensor and a working metal sensor running at a distance of 7 cm. The monitoring system with an internet of things (IOT)-based android smartphone uses the blynk application on a smartphone, which is directly connected to the monitoring system for the number of people and the metal detection system functions by proving the number of people and an alarm if there is metal